Seaweed sulphated polysaccharide as an inhibitor of calcium oxalate renal stone formation. (December 2016) - Bhadja, Poonam; Lunagariya, Jignesh; Ouyang, Jian-Ming
Graphical Abstract: Abstract: Sulphated polysaccharides (SPSs) from various seaweeds possess broad spectrum therapeutic and biomedical properties that are known to play a significant inhibitory role in calcium oxalate (CaOx) kidney stones. CaOx stone formation is a multistep process, which includes crystal nucleation, growth, aggregation, and crystal retention. Renal tubular cell injury is one of the determining factors leading to crystal retention and formation of stone in the nidus. In the present review, a comprehensive account was revealed on the therapeutic mechanisms of action of various seaweed SPSs on CaOx renal stone formation. Seaweed SPSs are inhibitor of crystal nucleation, growth, and aggregation. SPSs prevent renal tubular cell damage because of its antioxidant properties, thereby preventing crystal adherence and internalization. Seaweed SPSs are promising molecules because of their role in renal stone prevention. This study contributed much interest for researchers in a wide spectrum.